2023
DOI: 10.5114/kitp.2023.126097
|View full text |Cite
|
Sign up to set email alerts
|

Robotic thymectomy: a review of techniques and results

Abstract: Thymectomy is a well-established therapeutic option in the multidisciplinary treatment of nonthymomatous myasthenia gravis (MG) and in thymoma treatment. Although many surgical procedures for thymectomy have been identified, the transsternal method is still regarded as the gold standard. Minimally invasive procedures, on the other hand, have achieved popularity in the last decades and are now extensively used in this field of surgery. Among them, robotic thymectomy has been the most cutting-edge surgical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…However, thymectomy may be considered in children with generalized MG with positive acetylcholine receptor anti-receptor serology who do not respond satisfactorily to pyridostigmine therapy or immunosuppressive therapy. There may also be an indication for thymectomy in children for whom it is necessary to prevent possible complications of immunosuppressive therapy [ 34 ].…”
Section: Indications For Thymectomymentioning
confidence: 99%
“…However, thymectomy may be considered in children with generalized MG with positive acetylcholine receptor anti-receptor serology who do not respond satisfactorily to pyridostigmine therapy or immunosuppressive therapy. There may also be an indication for thymectomy in children for whom it is necessary to prevent possible complications of immunosuppressive therapy [ 34 ].…”
Section: Indications For Thymectomymentioning
confidence: 99%
“…W analizie największych serii tymektomii wykonywanych przy użyciu robotów wykazano wysoki profil bezpieczeństwa zabiegów RATS oraz mniejszą liczbę powikłań (na poziomie 1,6-7,2%, z których najczęstsze to: chłonkotok, krwawienie i przełom miasteniczny), mniejszą śródoperacyjną utratę krwi i skrócenie czasu hospitalizacji w porównaniu z operacją metodą otwartą. Ponadto tymektomia wykonywana metodami małoinwazyjnymi RATS i VATS jest porównywalna pod względem doszczętności zabiegu, liczby powikłań, czasu hospitalizacji i odsetka konwersji do sternotomii [28]. W 2016 r. Wolfe i wsp.…”
Section: Rodzaje Dostępu Chirurgicznego W Resekcji Grasicy I Wynikiunclassified
“…In fact, the robotic platform has enabled increased expertise in dissection and reconstruction of delicate structures. Currently, numerous papers have demonstrated that the use of robotic assistance in thoracic surgery (RATS) can help optimize outcomes and maximize patient benefits in a variety of neoplastic and non-neoplastic diseases [2,3]. The advantages of RATS can be listed as follows: (1) improved vision thanks to the 10 times magnification and the depth perception of its 3D high-definition camera, (2) seven degrees of freedom (7DOF) allowing complex surgical maneuvers to be performed safely, reaching comfortably narrow spaces, (3) tremor filtering (6-Hz motion filter) and motion scaling systems that counteract physiologic hand tremors, allowing the surgeon to perform the finest surgical movements, (4) surgeon ergonomic position reducing fatigue and muscular struggle, (5) Firefly (fluorescence-capable vision system), which offers integrated high-resolution near-infrared fluorescence images in 3-dimensional vision, taking advantage of this technology to identify vascular anatomy.…”
Section: Introductionmentioning
confidence: 99%